ANALISA PENGARUH VARIASI TEBAL PLAT ALUMINIUM PADA DC INVERTER DENGAN WAKTU TERHADAP TEGANGAN LISTRIK PADA BLOK MESIN HONDA CB - Martini, Ninik; Zaenudin, Akhmad (MEKANIKA: Jurnal Teknik Mesin, 2015)
Starting from the daily grind that use motor vehicles for work, college, touring and also the use of a smartphone / handphone are already obliged to carry anywhere. When the researchers drive and use a smartphone /mobile phone while traveling, researchers imagined problems smartphone battery / handphone that need filled, ifusing the power of banks and even then only to help a moment, for that is the idea in the course of using a motorvehicle as well to fill the batteries of smartphones at once, but do not overload electrical vehicle itself. Therefore,researchers thought why do not utilize heat energy vehicle engine as a source of electrical energy, for theresearchers tried to create a tool to convert the heat engine into electrical energy that is efficient to use fill thebatteries smartphone / mobile phone while traveling, Dc inverter is a device to increase the voltage of the lowvoltage dc power becomes greater. Researchers used thermoelectrically (Peltier) as a producer of electric voltageby utilizing engine heat is wasted through the medium of an aluminium plate as a heat sink, so it can be used tocharge the battery power bank or smartphone. In the study researchers used three (3) aluminium plate thicknessvariation of 2.3 and 4mm at the time of testing 2,4,6,8 and 10 minutes. From research to engine speed 1100 rpm for10 minutes and the heat sink as a cooling medium thermoelectrically. Then obtained the rate of transfer of heatconduction and convection heat transfer rate on the 2mm thick aluminium plate that is qk = 10078, w and w qc =0.38, so that the rate of heat transfer is conduction and convection heat transfer rate of most good.Keywords: Conduction , convection , thermoelectri